Effective leaders in entrepreneurial organizations build cultures that lead to high-performance outcomes. Issue 3 (1st October 2020) - El Tarabishy, Ayman
ABSTRACT: The two crucial questions within entrepreneurship research are if entrepreneurs affect organizational performance, and if so, what specific strategies are employed by such entrepreneurs that generate high-level performance. This study tested the hypothesis that in entrepreneurial organizations, the culture that leaders construct leads to performance outcomes. Data on leaders' culture-building actions in 31 entrepreneurial firms were obtained from organization members. The measure of culture, using a well-validated assessment questionnaire, was obtained from the leaders. A year later, these chief executive officer leaders provided performance data. The study then tested whether the culture mediated the effects of leaders' culture-building actions on organizational performance. The mediating analyses conducted to support a causal path, suggesting that in entrepreneurial organizations, it is the entrepreneurial culture, initiated by the leader's actions, that mediates the enhancement of organizational performance outcomes.